Uncovering the geographical and host impacts on the classification of Vibrio vulnificus. (20th February 2018) - Yu, Shoukai
Abstract: Vibrio vulnificus causes human sickness throughout the world via the consumption of undercooked seafood or exposure to contaminated water. Previous attempts at phylogenetic analyses of V. vulnificus have proven unsuccessful, mainly due to the poorly understood impact of factors on its divergence. In this study, we used advanced statistical and phylogenetic methods to strengthen the classification of V. vulnificus . This updated classification included the impact of geographical and host factors. The results demonstrate the existence of hierarchies and multidimensional effects in the classification of V. vulnificus, from the molecular level using biotypes, to the distributional level using geographical location, to the adaptational level through host immune response. These findings have implications for the classification of bacteria, bacterial evolution, and public health.